Dutch MNE Foreign Expansion into Developed and Developing Economies - Williams, Christopher; Martinez, Candace; Gastelaars, Elwin; Galesloot, Lars; van de Kerke, Dante (Management international / International Management / Gestiòn Internacional, 2011)
We investigate the differences in entry mode strategy for MNEs from a highly developed country (The Netherlands) when expanding abroad into locations in developed and developing economies. Our analysis is based on 544 foreign expansion decisions by MNEs listed on the Amsterdam Exchange Index (AEX) over the five-year period 2004-2008 inclusive. We find that when expanding into other developed countries, cultural distance plays a key role in MNE location strategy; institutional quality of the location is not relevant. When expanding into less developed economies, however, cultural distance becomes irrelevant and the effects of institutional quality become stronger.